2011
DOI: 10.5296/bms.v3i1.904
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Employees Motivation on Organizational Effectiveness

Abstract: The purpose of this paper is to identify the factors that effects employee motivation and examining the relationship between organizational effectiveness and employee motivation.A model was designed based on the literature, linking factors of employee motivation with employee motivation and organizational effectiveness. Three hypotheses were build based on the literature and the model and were tested in perspective of the previous studies and literature.The literature and various studies concluded that factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
2
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(162 citation statements)
references
References 3 publications
10
134
2
16
Order By: Relevance
“…Mangkunegara (2013) states that motivation is one of the factors that affect the performance achievement. Manzoor (2012) comments that the stronger the work motivation, the higher the employees' performance is. The increases in employees' motivation will provide a significant enhancement for improving the employees' performance in carrying out their work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mangkunegara (2013) states that motivation is one of the factors that affect the performance achievement. Manzoor (2012) comments that the stronger the work motivation, the higher the employees' performance is. The increases in employees' motivation will provide a significant enhancement for improving the employees' performance in carrying out their work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it indicated that there is something needs to be developed and involve in this practice. Because of in a service-oriented business training and capacity building program for the employees for their improvement of skill and perpetual development are essential due to; customer's trends and expectations constantly changed [21,53]. Therefore, providing employees with the possibility to develop their individual potential to the maximum contributes to the success and competitiveness of the enterprise is the basic thing.…”
Section: Questions/itemsmentioning
confidence: 99%
“…Manzoor added that no other incentives or motivational technique comes closer to money in regarding to influential value to the employees work performance. Manazoor again found that; one of the employee's motivational factors for the employee's satisfaction and work performance is competitive salary [53]. Logically, employees who perceive their jobs to be secure and competitive, it offers very committed workers and be "happier" and contribute for the financial and the overall performance of their hotels/lodges.…”
Section: Questions/itemsmentioning
confidence: 99%
“…In line with this assertion, Finck et al (1998) postulate that companies must recognize the human factor as an important ingredient for organisational success and survival, since business excellence can only be achieved when employees are excited and motivated by their work. Rutherford (cited in Manzoor, 2012) opines that motivation defines the success of an organisation because provoked employees are constantly looking for improved practices to do a work, so it is essential for organisations to increase the motivation of their employees. To this end, since employee performance is a joint function of ability and motivation, one of management's primary tasks, therefore, is to motivate employees to perform to the best of their ability (Moorhead and Griffin, 1998;Mullins, 2010).…”
Section: Work Motivationmentioning
confidence: 99%